The Effect of Investment and Development Expenditure on Poverty Levels Mediated By The Level of Income Inequality in Balikpapan City - Berlina Puspayanti; Rahcmad Budi Suharto; Diana Lestari (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of investment and development expenditure on poverty levels in Balikpapan City, considering the mediating role of income inequality. The research employs a quantitative approach using path analysis to examine both direct and indirect relationships among variables. The data used are secondary data from 2013 to 2023, including investment, development spending, the Gini index, and poverty rates. The results show that investment and development expenditure have a direct impact on both income inequality and poverty. Moreover, income inequality mediates the influence of investment and development expenditure on poverty. This study provides important implications for local government in formulating more effective and equitable development policies to reduce inequality and alleviate poverty in urban areas.